The impact of the images in multiple-choice questions on anatomy examination scores of nursing students - Narnaware, Yuwaraj; Cuschieri, Sarah (My University, 2023)
Visualizing effects of images on improved anatomical knowledge are evident in medical and allied health students, but this phenomenon has rarely been assessed in nursing students. To assess the visualizing effect of images on improving anatomical knowledge and to use images as one of the methods of gross anatomical knowledge assessment in nursing students, the present study was repeated over two semesters. The results show that the percent class average (%) was significantly (P<0.006) increased with the inclusion of more anatomical images in a multiple-choice anatomy exam compared to a similar exam with fewer images and was significantly (P<0.002) decreased by reducing the number of images by 50% compared to image-rich exams. However, examinations with an equal number of images did not alter the class average. The percent score of individual questions from the examinations with images plus text was significantly (P<0.001) higher than the same questions with text only in both semesters. The findings of this study indicate that image inclusion in anatomy examinations can improve learning and knowledge, may help reduce cognitive load, recall anatomical knowledge, and provide a hint to an exam question.
Keywords: anatomy; physiology; images; visualization; nursing; knowledge retention; technology